STUDI EKSPERIMENTAL EFEK ANALGETIK INFUS AKAR TEKI (Cyperus rotundus Linn) PADA HEWAN COBA (MENCIT)* - Dwi Sutiningsih; Martini - (Universitas Muhammadiyah Semarang, 2007)
Background: Traditional medicines have less or even no side-effect, are easy to get, and are relatively low price. There are many kinds of plants which are used as medicine material; one of them is teki root or Cyperusrotundus Linn which can be used as an analgesic to relieve pain. Objective ofthe research is to find out how far the ffict of teki root extract as an analgesic with various concentrations on mice is. Method used is bycollecting 30 mice, which are divided into 5 groups wilh 6 mice for each. Group I as control group is treated with aquades 0,5 ml for each; group II as standard of comparison is treated with aspirin 200 mg/kg BW foreach; group III, IV, and V are treated with intake of teki root extract 5%, l0%, and 20%,for each. All treatments and controls are done orally and 15 minutes later, mice reaction-time on hot plates in 5J 13 ,s counted. Result of the research is that the average of mice reaction-time in group I is I 1,46 t 0,55 second; group II is 28,50 + 1,28 second; group III is 16,32 !0,42 seconcl; group IV is 17,38 ! 0,54 second; and group V is 22,75 t 0,8 I second. Statistical test with Varian Analysis Method (P<0,05) and Tuck:y Test result show there is significance of treated group toward control group. In conclusion, based on the research teki root extract has an analgesic effect. Teki root extract in 2A% concentration has the largest effect among treated g'oups and if compared with aspirin the analgesic effect is 0,66 times.Keywords: Cyperus rotundus, analgesic effect, extract, mice